2017
DOI: 10.1016/j.apcatb.2016.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Fe/ZSM-11 as a novel and efficient photocatalyst to degrade Dichlorvos on water solutions

Abstract: Iron modified ZSM-11 zeolites were tested as heterogeneous catalysts in the photodegradation of Dichlorvos water solutions. ZSM-11 zeolite matrixes were synthesized by the hydrothermal method and iron was incorporated by the wet impregnation method in four different concentrations. Catalysts samples were characterized by several techniques (XRD, BET, UV-vis DRS, ICP-OES, TPR, EPR) in order to confirm structure, crystallinity and iron species present. a-Fe 2 O 3 was detected by XRD in higher iron content sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 51 publications
1
12
0
1
Order By: Relevance
“…From Fig. 3C, for KA-NRS and KA-SFNS support, the band at around 241.8 nm was assigned to Al-O charge-transfer transition of four-coordinated framework, which refers to structures with highly ordered octahedral symmetry and stabilized in the framework of silica [33]. This band shifts toward high energy of 257.2 nm after loading Pt nanoparticles due to Al-O-Pt [34].…”
Section: Uv-vis and Ramanmentioning
confidence: 91%
“…From Fig. 3C, for KA-NRS and KA-SFNS support, the band at around 241.8 nm was assigned to Al-O charge-transfer transition of four-coordinated framework, which refers to structures with highly ordered octahedral symmetry and stabilized in the framework of silica [33]. This band shifts toward high energy of 257.2 nm after loading Pt nanoparticles due to Al-O-Pt [34].…”
Section: Uv-vis and Ramanmentioning
confidence: 91%
“…Figure 1 showed the powder X‐ray diffraction patterns for various MEL zeolite samples; it was observed that all the synthesized samples exhibited the characteristic peaks (such as 2θ = 7.9, 8.8, 14.8, 23.1, and 23.9°) of an MEL topologic framework, 23,24 indicating that the MEL zeolites were successfully fabricated in the present work. No other detectable diffraction peaks for metal phases, such as large iron oxides, were found, which indicated a substantial absence of large metal crystallites.…”
Section: Resultsmentioning
confidence: 76%
“…Como puede observarse, el aumento del contenido hierro genera una disminución del área superficial de los nanotubos. Este efecto es atribuido al bloqueo que produce la agregación de la fase activa sobre la superficie interna del nanotubo (Gomez et al, 2017). El contenido de Fe en los nanomateriales, determinada por AA, fue muy similar a la cantidad teórica.…”
Section: Resultados Y Discusiónunclassified